Determinants of attitude towards celebrity brand and purchase intention - Atiqah, Shuib (2021)
Recently, celebrities have begun to venture into business. It has become a trend among celebrities to have their businesses, namely celebrity entrepreneur endorsement. However, studies in the context of celebrity entrepreneur are still limited. Hence, this study was conducted to develop the concept of celebrity entrepreneur endorsement by investigating the relationship of the credibility of a Celebrity, Brand, Advertisement, and Self-Brand Connection. In addition, Attitude toward the Brand acts as the mediator in shaping consumer's approach of Purchase Intention. Celebrity entrepreneur endorsement proves that their credibility can enhance customers' attitude and purchase intentions towards a celebrity brand. This study adopted the quantitative research by conducting an online survey. Data were collected among generation Y in northern Malaysia aged between 25 to 40. Approximately 395 respondents responded to the survey, with a response rate of 82%. The total numbers of samples for this study were 3 51 respondents after data cleaning. The findings of this study show the significant influence of the credibility of celebrity, brand and self-brand connections to purchase intentions, which are mediated by attitudes towards the brand. Theoretical framework and methodological approach were discussed, and several suggestions for future research were identified and recommended. In short, this study helps to further understand the purchase intention in celebrity entrepreneurship context.